Multimedia Interaktif Berbasis Articulate Storyline 3 Sebagai Alternatif Media Pembelajaran Materi Karakteristik Geografis Indonesia di Sekolah Dasar - Dwi Novia Rachmawati; Ita Kurnia; Alfi Laila (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
The study was conducted based on observations at SDN Sukorame 2 Kediri, which showed that as many as 69.09% of students in Grade V on Indonesian geographical characteristics obtained scores below KKM (Minimum Criteria of Mastery Learning). This problem occurred because of the incompleteness of the material presented in learning resources and no learning media that could clearly describe the geographical characteristics of big islands in Indonesia. In addition, the information obtained that as many as 96.36% of students prefer digital-based learning resources equipped with writing, images, sound, and animation. However, SDN Sukorame 2 Kediri currently still lacked of digital-based learning resources. Based on problem analysis and needs analysis, researchers will develop interactive multimedia by utilizing Articulate Storyline 3 software. This research and development aim to produce innovation in learning activities to be more effective in the form of interactive multimedia that helps students understand the material and increase motivation in learning. This research uses the R&D method with the ADDIE model. The results of this study showed that the validity of material experts was 90% and media experts were 82%, so the average validation results were 86%. The practical results of the questionnaire of expert responses of limited-scale practitioners are 91% and broad-scale practitioner experts are 95%, so an average practical result of 93% is obtained. The results of effectiveness on a limited scale of 84 and extensive trials of 82 so that it is known that student learning outcomes after using interactive multimedia are higher than before the use of multimedia. Based on the data from the validity, practicality and effectiveness test results, it can be concluded that interactive multimedia by utilizing Articulate Storyline 3 is valid, practical and effective use.